Could a Different View of Quiescence Help Us Understand How Neurogenesis Is Regulated? - Urbán, Noelia (Frontiers in Neuroscience, 2022)
The majority of adult neural stem cells (aNSCs) are in a distinct metabolic state of reversible cell cycle exit also known as quiescence. The rate of aNSC activation determines the number of new neurons generated and directly influences the long-term maintenance of neurogenesis. Despite its relevance, it is still unclear how aNSC quiescence is regulated. Many factors contribute to this, like aNSC heterogeneity, the lack of reliable quiescence markers, the complexity of the neurogenic niches or the intricacy of the transcriptional and posttranscriptional mechanisms involved. In this perspective article I discuss possible solutions to these problems. But, first and foremost, I believe we require a model that goes beyond a simple transition towards activation. Instead, we must acknowledge the full complexity of aNSC states, which include not only activation but also differentiation and survival as behavioural outcomes. I propose a model where aNSCs dynamically transition through a cloud of highly interlinked cellular states driven by intrinsic and extrinsic cues. I also show how a new perspective enables us to integrate current results into a coherent framework leading to the formulation of new testable hypothesis. This model, like all others, is still far from perfect and will be reshaped by future findings. I believe that having a more complete view of aNSC transitions and embracing their complexity will bring us closer to understand how aNSC activity and neurogenesis are controlled throughout life.